Performance of Chrysanthemum (Chrysanthemum morifolium Ramat.) in Terai Region of West Bengal - Sidhya, P.; Sarkar, D.; Sarkar, I.; Maitra, S.; Pal, S. (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was carried out at Instructional Farm, Department of Floriculture, Medicinal and Aromatic Plants in Uttar Banga Krishi Viswavidyalaya, West Bengal, India during July, 2018 to February, 2020 at Terai region of West Bengal, India to evaluate the suitable spray chrysanthemum genotypes for commercial cultivation. The experiment was laid out in completely randomized design twice replicated. Fourty different genotypes of spray chrysanthemum were evaluated based on their growth and flowering parameters. Considering the vegetative growth, Local Yellow-2 showed the maximum number of branches (12.04) in pooled whereas Marigold recorded the minimum (6.82). The genotypes Arka Usha Kiran showed the maximum vase life of 11.69 days while Arka Pink Star recorded the minimum (6.64). Genotypes including Jaya, Vasanthika, Marigold, Local Yellow-2, White Prolific, and A1 collection were considered good for cut flowers, whereas Yellow Baby, White Anemone, Usha Kiran, Aparajita, Basanti, Bidhan Antara, Sweata Singar, and White Dolley were used for the production of loose flowers. Arka Yellow Gold reported the maximum days for first flower full blooming of 143.82 and 144.60 days in the second year and pooled respectively while in the first year Sweta Singar reported the maximum days for first flower full blooming. The minimum days for first flower full blooming was observed in Geetanjali in second year and pooled respectively while in the first year Jaya reported the minimum days for first flower full blooming.